Analisis Bibliometrik Perkembangan Penelitian Preservasi Naskah Kuno di Perpustakaan - Clarissa Prameswari; Tamara Adriani; Frans Asisi Datang; Muhamad Prabu Wibowo (Universitas Sebelas Maret Library, 2024)
Preserving manuscripts is crucial to maintaining a nation's cultural heritage and historical knowledge. Manuscript collections have a high risk of damage, and preservation is the primary responsibility of various parties, including libraries. Although several studies have been carried out regarding preserving manuscripts in Indonesia, research has yet to examine this trend globally. Therefore, this study uses bibliometric analysis to explore the development of research trends regarding the preservation of manuscripts in libraries. The research was carried out on November 14, 2023, by searching the Scopus database using the keywords preservation, manuscript, and library. Data were analyzed using the VOSViewer application to determine a bibliometric map of research developments regarding the preservation of manuscripts in libraries. The research results show that (1) there are 134 publications on manuscript preservation in libraries tend to increase, (2) overview of research trends in the preservation of manuscripts in libraries divided into clusters of manuscripts, historic preservation, and digitization, (3) The United States is the most productive country in international publications, (4) the University of Indonesia is the most contributive institution in international publications, and (5) topics such as historical documents, digital storage, deterioration can be researched in the future. This research will provide insight into research topics that can be explored further.